A map matching algorithm for GPS tracking data - Li, Qingquan; Huang, Lian (Ce hui xue bao, 2010)
Map matching GPS floating car tracking data is different from that for traditional navigation system according to the specific application. With the consideration that GPS floating car tracking data provide a global moving trend, using drive constraints in city road networks, this paper proposed a novel map matching method based on road connectivity under geometric topology and traffic control constraints as well as the similarity between the curve of trajectory and the outline of road paths. This algorithm can obtain good map matching results and was validated through experiments, and finally can support the further analysis and application of GPS floating car data.